Facebook, Instagram or Tiktok? - on the performance of advertising channels in dropshipping - Dengler, Simon Thomas (2021)
As part of ecommerce, drop shipping as an industry has grown in popularity in recent years. However, marketingin drop shipping has barelybeen subject to academic research so far. In particular, online advertising channels used in drop shipping represent uncharted scientific territory. Thus, the research “Facebook, Instagram or TikTok? –On the Performance of Advertising Channels in Drop shipping” intends to find out which online advertising channels in drop shipping perform the best. Based on the analysis of survey data, this research shows that Google Ads and email retargeting are the best performing online advertising channels in drop shipping.